Lung sounds in neonates with and without an added dead space - Blowes, R. W.; Milner, Anthony David; Yiallouros, Panayiotis K. (My University, 1995)
Previous studies have reported great difficulty in recording lung sounds from neonates and have found conflicting results. We studied lung sounds in neonates during the inspiratory phase of the respiratory cycle as monitored by inductive plethysmography (A) and by pneumotachograph and face mask (8) which added dead space of 12 mL. Sixteen term babies were tested 12 hr to 6 days (median 45 hours) after birth. Lung sounds were recorded and then analysed using overlapping and nonoverlapping fast Fourier transforms. The two methods of analysis showed difference in intensity but not in frequency. Fourteen babies provided enough breaths for comparison; total of 596 inspirations were analysed. The intensity of lung sounds on occasion B was higher in all but two babies with mean B/A ratio of 2.4. The mean (SD) power on occasions A and B was 13.9(8.5) mW and 26.9 (21.0) mW, P = 0.02, respectively. In all but 4 babies the B/A ratios of the median (f50) and 90th centile (f90) frequencies were scattered randomly within 20% of unity. The mean (SD) f50 on occasions A and B was 205.5 (51.1) Hz and 225.8 (32.3) Hz, P = 0.10, respectively; the mean f50 was 370.3 (91.0) Hz and 396.1 (67.8) Hz, P = 0.25, respectively. Linear regression showed that there is third-order polynomial relationship between sound intensity and air flow at the mouth. A weaker positive association exists between frequency and air flow, showing that the median and 90th centile frequencies approach an asymptote as flow increases. We conclude that adding dead space increases the intensity of lung sounds in neonates due to increased flow, but has no consistent effect on frequency content.
Keywords: Lung sounds; Neonates; Auscultation